Digital marketing strategies and models for competitive business - Mota Pinto, Filipe; Guarda, Teresa, 1966- (Advances in business strategy and competitive advantage., 2020)
""This book explores the theory and application of digital marketing strategies and models in businesses"--Provided by publisher"--